2023
DOI: 10.3389/fimmu.2023.1164724
|View full text |Cite
|
Sign up to set email alerts
|

Turicibacter and Acidaminococcus predict immune-related adverse events and efficacy of immune checkpoint inhibitor

Abstract: IntroductionImmune checkpoint inhibitors have had a major impact on cancer treatment. Gut microbiota plays a major role in the cancer microenvironment, affecting treatment response. The gut microbiota is highly individual, and varies with factors, such as age and race. Gut microbiota composition in Japanese cancer patients and the efficacy of immunotherapy remain unknown. MethodsWe investigated the gut microbiota of 26 patients with solid tumors prior to immune checkpoint inhibitor monotherapy to identify bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
0
12
1
Order By: Relevance
“…This observation was corroborated by another investigation involving 34 patients, indicating an inverse relationship between the prevalence of the Bacteroidetes phylum and the onset of CTLA4‐related colitis 139 . More recently, Hamada et al 149 . observed a higher abundance of Turicibacter and Acidaminococcus in the group of patients experiencing irAEs.…”
Section: Mechanisms Of Ici‐induced Iraes In Nsclcmentioning
confidence: 55%
See 2 more Smart Citations
“…This observation was corroborated by another investigation involving 34 patients, indicating an inverse relationship between the prevalence of the Bacteroidetes phylum and the onset of CTLA4‐related colitis 139 . More recently, Hamada et al 149 . observed a higher abundance of Turicibacter and Acidaminococcus in the group of patients experiencing irAEs.…”
Section: Mechanisms Of Ici‐induced Iraes In Nsclcmentioning
confidence: 55%
“…148 This observation was corroborated by another investigation involving 34 patients, indicating an inverse relationship between the prevalence of the Bacteroidetes phylum and the onset of CTLA4related colitis. 139 More recently, Hamada et al 149 observed a higher abundance of Turicibacter and Acidaminococcus in the group of patients experiencing irAEs. These findings collectively imply a potential mechanistic association between particular bacterial groups in the gut microbiota and irAEs, offering a promising target for novel anti-tumour immunotherapy.…”
Section: Gut Microbiome Metabolic Pathways Associated With Iraesmentioning
confidence: 98%
See 1 more Smart Citation
“… 24 These IDO inhibitor-treated animals, although they had a median survival slightly higher than the controls, their biota had significant levels of Turicibacter , which were not detected in the naive and PBS-treated animals but that certainly had to be present in the community to increase its abundance in this group. This taxon, often associated with a healthy host, including probiotic properties, has been found in association with ICI response 36 and anti-inflammatory effects. 37 …”
Section: Discussionmentioning
confidence: 99%
“…Mann et al., in the in-cell line study, showed that microbiota via Toll-like receptor 2 may directly modulate the expression of PD-L1 in HNCs. In addition, the effect of the gut microbiome in response to ICIs was proven in many different types of epithelial tumors ( Routy et al., 2018 ; Zheng et al., 2019 ; Hamada et al., 2023 ). Currently, some studies registered in the Clinicaltrials.gov registry try to address directly or indirectly the issue of the link between microbiome in immunotherapy response (e.g., NCT05375266: recruiting, NCT05083416: active, not recruiting), which ought to be followed.…”
Section: Immunotherapymentioning
confidence: 99%